The Teacher’ Roles in Remote English Teaching - Ni Kadek Windani; I G A Lokita Purnamika Utami; Luh Gede Rahayu Budiarta (International Journal of Language and Literature, 2023)
Distance learning faces challenges in terms of communication and interaction, which results in teachers being unable to carry out their roles optimally. Although many studies have discussed the role of teachers, studies that specifically explore the role of teachers in distance English teaching at the senior high school level are still limited. This study aims to identify the role of teachers in online (distance) English teaching in senior high schools. This study uses a descriptive qualitative method with English teachers from SMA 1 Semarapura and SMA Pariwisata Saraswati Klungkung as subjects. Data were collected through observation and interviews, then analyzed using Harmer's theory in 2001 on the role of teachers in the teaching and learning process, which includes eight roles: controller, organizer, assessor, prompter, resource, participant, tutor, and observer. The results of the study indicate that although teachers play all of these roles, the implementation of roles in the context of distance learning is not optimal. Therefore, it is necessary to optimize the role of teachers to improve the quality of distance teaching.